2023
DOI: 10.1002/edn3.408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in an endangered fish Gnathopogon caerulescens using environmental DNA and its potential use in fish conservation

Abstract: Gnathopogon caerulescens, an endemic fish of Lake Biwa, Japan, is one of the most important fishes for lake fisheries. It has been listed as an endangered species following its population decline in the 1990s and thus needs conservation. An increasing number of studies have recently stressed on the importance of incorporating genetic diversity for conservation purposes. In this study, we aimed to evaluate the mitochondrial DNA haplotype composition of G. caerulescens using environmental DNA (eDNA) to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 100 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…In contrast, studies targeting macro-organism's (e)DNA including fish and amphibians have mainly used mtDNA fragments and research interest in nuDNA is still limited. Some recent studies have challenged eDNA-based genetic diversity monitoring targeting aquatic vertebrates, but most of them were also based on mtDNA (Sigsgaard et al 2016;Wakimura et al 2023; but see Andres et al 2021). While recent substantial advance of next-generation sequencing (NGS) technology has drastically reduced sequencing costs (Goodwin et al 2016), achieving database enrichment and developing a framework for sharing data among the science communities will require further collaborative efforts of multiple researchers and laboratories in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies targeting macro-organism's (e)DNA including fish and amphibians have mainly used mtDNA fragments and research interest in nuDNA is still limited. Some recent studies have challenged eDNA-based genetic diversity monitoring targeting aquatic vertebrates, but most of them were also based on mtDNA (Sigsgaard et al 2016;Wakimura et al 2023; but see Andres et al 2021). While recent substantial advance of next-generation sequencing (NGS) technology has drastically reduced sequencing costs (Goodwin et al 2016), achieving database enrichment and developing a framework for sharing data among the science communities will require further collaborative efforts of multiple researchers and laboratories in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the detection of rare haplotypes, the authors recommend sampling multiple populations since haplotypes that may be rare at one site could be common at another. Meanwhile, Wakimura et al (2023) recognize that obtaining detailed genetic information from eDNA samples requires overcoming several challenges to successfully target and extract low-abundance DNA markers in a reliable and repeatable manner. The authors make progress on this by developing a high throughput sequencing approach to accurately discriminate chimeric and erroneous sequences without limiting the detection of rare haplotypes.…”
Section: Environmental Dna a S A Source Of P Opul Ati On -Le Vel G En...mentioning
confidence: 99%
“…While some of these limitations are inherent, others may be overcome through technological or methodological improvements. For example, research byAdams et al (2023) andWakimura et al (2023) provides valuable insight into the issues of sensitivity and reliability of population genetic data obtained from eDNA samples and suggests methods for improvement.…”
mentioning
confidence: 99%
“…In eDNA metabarcoding, gene frequencies can be obtained as relative read counts instead of numbers of individuals or alleles. Despite differences in the nature of the obtained data, previous studies performed in tanks or even in the field have shown a good congruence in gene frequencies (typically as haplotype frequencies) between eDNAand tissue-based approaches (Andres et al, 2021;Couton et al, 2023;Marshall & Stepien, 2019;Sigsgaard et al, 2016;Wakimura et al, 2023). Therefore, it should be possible to calculate frequency-based statistics used in landscape genetics.…”
mentioning
confidence: 99%
“…The PCR conditions were initial denaturation at 94°C for 2 min and 35-40 cycles of denaturation at 94°C for 15 s, annealing at 63°C for 30 s, and extension at 68°C for 30 s. The number of cycles was initially 35, and samples for which no target peak was identified by electrophoresis after the second-round PCR (2nd PCR) were analysed again at 38 cycles and then 40 cycles (TableS1). The number of PCR cycles was kept modest to minimize errors(Wakimura et al, 2023). The first PCR was conducted with eight replicates per sample (20 μL × 8), and individual replicates were pooled and purified using 160 μL of VAHTS DNA Clean Beads (Vazyme Biotech, Nanjing, China) as templates for the second PCR.…”
mentioning
confidence: 99%